Identification of biological pathways regulated by PGRN and GRN peptide treatments using transcriptome analysis. (9th July 2016) - Rollinson, Sara; Young, Kate; Bennion‐Callister, Janis; Pickering‐Brown, Stuart M.
Abstract: Mutations in progranulin (PGRN) have been linked to two neurodegenerative disorders, heterozygote mutations with frontotemporal lobar degeneration (FTLD) and homozygote mutations with neuronal ceroid lipofuscinosis (NCL). Human PGRN is 593aa secreted growth factor, made up of seven and a half repeats of a highly conserved granulin motif that is cleaved to produce the granulin peptides A–G and paragranulin. While it is thought that PGRN protects against neurodegeneration through its role in inflammation and tissue repair, the role of PGRN and granulins in the nervous system is currently unclear. To better understand this, we prepared recombinant PGRN, granulin A‐F and paragranulin, and used these to treat differentiated neuronal SH‐SY5Y cells. Using RNA sequencing and bioinformatics techniques we investigated the functional effects of PGRN and the individual granulins upon the transcriptome. For PGRN treatment we show that the main effect of short‐duration treatments is the down‐regulation of transcripts, supporting that signalling pathway induction appears to be dominant effect. Gene ontology analysis, however, also supports the regulation of biological processes such as the spliceosome and proteasome in response to PGRN treatment, as well as the lysosomal pathway constituents such as CHMP1A, further supporting the role of PGRN in lysosomal function. We also show that the response to granulin treatments involves the regulation of numerous non‐coding RNA's, and the granulins cluster into groups of similar activity on the basis of expression profile with paragranulin and PGRN having similar expression profiles, while granulins B, D, E and G appear more similar. Abstract : Transcriptome analysis demonstrated that treating neural differentiated SH‐SY5Y cells with PGRN and the granulins that the majority of genes were down‐regulated, with a role in spliceosome, proteasome and lysosomal function implicated for PGRN.